Contrast enhanced renal MR angiography at 7 Tesla: How much gadolinium do we need?. Issue 86 (January 2017) - Beiderwellen, Karsten; Kraff, Oliver; Laader, Anja; Maderwald, Stefan; Orzada, Stephan; Ladd, Mark E.; Forsting, Michael; Lauenstein, Thomas C.; Umutlu, Lale
Abstract: Objectives: To investigate whether a dose reduction of Gadobutrol for renal magnetic resonance angiography (MRA) at 7 Tesla (T) is feasible while preserving diagnostic image quality. Methods: Ten healthy volunteers were enrolled for a renal MRA on a 7 T scanner. Fast low angle shot (FLASH) MRA data sets were obtained utilizing three different doses of Gadobutrol (0.1, 0.05 and 0.025 mmol/kg body weight [BW]). Contrast ratios (CR) were measured in the aorta as well as in the intra- and extraparenchymal arteries compared to the psoas muscle. Qualitative analysis regarding the delineation of vessel structures was performed using a four-point-scale. Results: All doses of Gadobutrol allowed for a good delineation of the aorta and renal arteries. For the extra- and intraparenchymal segmental arteries higher values were observed for full and half dose in comparison to quarter dose. No significant difference was observed for full and half dose. A lower CR was observed for quarter compared to half dose (p < 0.05) for the renal arteries. Conclusions: While best results were observed for half and full dose, a dose reduction to 0.025 mmol/kg BW is justifiable, maintaining a diagnostic image quality. This may be of high interest considering patients with renal impairment.